How does student creativity depend on teaching methods at the institute? Modern information technologies for education and creativity as manifestations of the specifics of the psyche - Ainash Davletova; Aidana Nazarova; Ainash Alzhanova; Yuliya Lazareva (Cogent Education)
This study analyzes the impact of project-based learning (PBL) and SCAMPER techniques on fostering creativity among university students. PBL, a dynamic classroom approach, engages students in acquiring knowledge and skills through an extended inquiry process centered around complex, authentic questions and carefully created products and activities. The creative thinking method known as SCAMPER – which stands for Substitute, Combine, Adapt, Modify, Put to another use, Eliminate and Reverse – helps students explore novel solutions. We investigate how these student-centered teaching methods, along with personal characteristics like self-efficacy and adaptability in problem-solving, promote creativity in higher education environments. A total of 150 junior students participated in the study, collaborating on various structured group assignments through the Moodle platform. The study assessed students’ creative abilities and motivational orientations using the Torrance Test of Creative Thinking (TTCT), personality tests and the Work Preference Inventory (WPI). The research design employed a quasi-experimental approach to quantitatively and qualitatively investigate how instructional tactics influenced students’ creativity and problem-solving skills. The findings showed that PBL and SCAMPER greatly enhanced students’ flexibility, inventiveness and fluency. Improved creative performance was found to be positively correlated with characteristics like achievement orientation and self-efficacy. Additionally, the collaborative interactions made possible by digital platforms strengthened students’ creative outputs. These results imply that combining cutting-edge pedagogical approaches with digital tools might significantly improve student learning outcomes in fields like engineering and medical education, which place a high value on creativity and innovation.